THE DIFFERENCE OF - AHMAD ZULKIFLI, TOFANI I, BAHTIAR E W (SAGUNG SETO, 2009)
The purpose of this study is to evaluate the matrix metalloproteinase-8 (MMP-8) levels in a post-extraction dentai socket of Doxycycline (Dx) treated and non-treated mica. material and method. in this study, 24 male wistar mice were used. they were divided into three groups: 8 mica in non-treated/ control group (Group A), 8 mice were given 5 mg/ kg Dx 1 hour before and 7 days after the right upper incisor extraction (Group B), and 8 mice were given 2.5 mg/ kg Dx (Group C). the blood samples were taken fom the socket of the the extracted teethand being evaluated by ELISA to observe the MMP-8 level.result. MMP-8 level on the first day (Group C and control Group) were significantly different (p> 0.05). conclusion. Doxycycline treatment (2.5 mg/ kg) 1 hour before dental extraction has been proven to dacrease the average MMP-8 levels on mica.